Bridging theory and practice: National language policy and mother tongue documentation for effective implementation - Nwachukwu, Emmanuel lucas; Joseph, Christopher (Yayasan Mitra Persada Nusantara, 2024)
Language is a fundamental component of identity and culture, significantly shaping a nation's socio-political landscape. Recognizing this, nations continuously strive to preserve their indigenous languages. This paper explores the gap between theory and implementation in Nigeria’s national language policy, focusing on its role in preserving, revitalizing, and documenting mother tongues. It examines key challenges, including the scarcity of instructional materials and the shortage of qualified teachers for indigenous languages. The study highlights how effective implementation of the national language policy can extend mother tongue revitalization beyond formal education. Guided by the Language Ecology Model and David Crystal’s theory of language revitalization, this study employs a descriptive analytical methodology. By analyzing both current and historical data, it identifies critical gaps in policy execution. The findings emphasize that bridging the gap between policy and practice requires government commitment, particularly in resource allocation for instructional materials and teacher training. Furthermore, the study underscores that preserving and revitalizing endangered indigenous languages demands a holistic approach beyond classroom instruction. It calls for sustained efforts from governments and stakeholders to cultivate a cultural environment where indigenous languages are actively used and valued. Strategies such as fostering intergenerational language transmission, leveraging technology, and systematically documenting linguistic resources are essential. In conclusion, ensuring the successful implementation of Nigeria’s national language policy is a complex yet vital task. A comprehensive, multifaceted approach that integrates education, cultural engagement, and technological innovations is crucial to preserving linguistic heritage. This study advocates for increased policy-driven action to safeguard and promote indigenous languages, ensuring their survival and relevance in contemporary society.